Peranan Lingkungan Kerja dalam Meningkatkan Kinerja Karyawan di Perumda Tirta Musi Unit Pelayanan 3 Ilir Palembang - Itryah Itryah; Safira Shalsabila (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The work environment is one of the factors that plays an important role in improving employee performance, particularly in public service institutions. This community service activity aimed to describe the role of the work environment in enhancing employee performance at Perumda Tirta Musi Unit Pelayanan 3 Ilir Palembang. The methods used in this activity were observation and semi-structured interviews. The results showed that both the physical and non-physical work environments at Perumda Tirta Musi Unit Pelayanan 3 Ilir were conducive, as reflected by adequate work facilities, effective communication, harmonious working relationships, and strong managerial support. These conditions contributed to improved discipline, effectiveness, responsibility, teamwork, and employee productivity in delivering public services. The findings indicate that a conducive work environment plays a significant role in enhancing employee performance and improving the quality of public services.